Intravenous Contrast Medium Administration for Computed Tomography Scan in Emergency: A Possible Cause of Contrast-Induced Nephropathy - Lantam Sonhaye; Bérésa Kolou; Mazamaesso Tchaou; Abdoulatif Amadou; Kouméabalo Assih; Bidamin N’Timon; Kokou Adambounou; Lama Agoda-Koussema; Komlavi Adjenou; Koffi N’Dakena (Radiology Research and Practice)
The goal of this study was to assess risk for CIN after CT Scan during an emergency and to identify risk factors for the patient. Prospective review of all patients admitted to the emergency room (ER) of the Teaching Hospital of Lomé (Togo) during a 2-year period. CIN was defined as an increase in serum creatinine by 0.5 mg/dL from admission after undergoing CT Scan with intravenous contrast. A total of 620 patients underwent a CT Scan in the emergency room using intravenous contrast and 672 patients took the CT Scan without intravenous contrast. Out of the patients who received intravenous contrast for CT Scan, three percent of them developed CIN during their admission. Moreover, upon discharge no patient had continued renal impairment. No patient required dialysis during their admission. The multivariate analysis of all patients who had serial creatinine levels (including those who did not receive any contrast load) shows no increased risk for acute kidney injury associated intravenous contrast (odds ratio = 0.619, p value = 0.886); only diabetes remains independent risk factor of acute kidney injury (odds ratio = 6.26, p value = 0.031).